1999
DOI: 10.1046/j.1525-1497.1999.03199.x
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of syncope in hospitalized patients

Abstract: OBJECTIVE:To describe the etiologies of syncope in hospitalized patients and determine the factors that influence survival after discharge. lation-based studies from the 1980s underscored the importance of diagnosing the cause of syncope. 2-6 Individuals with syncope of cardiovascular origin had a higher 1-year mortality (18%-33%) than individuals with noncardiovascular or unexplained syncope (6%-12%), 2-6 and this increased risk continued for 5 years. 7 However, determining the etiology of a syncopal event wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(46 citation statements)
references
References 30 publications
4
41
0
1
Order By: Relevance
“…Whereas vasovagal syncope is associated with good prognosis,15 increased mortality for cardiac syncope and for syncope in patients with non-cardiac life-threatening illnesses17 has been demonstrated. It appears, however, that it is not the cause of syncope that imparts increased mortality risk, but age and comorbidities, including cardiovascular comorbidity 18 19. This ties in with the fact that a history of myocardial infarction, heart failure and high CCI are all predictors of syncope post pacemaker implant in our population.…”
Section: Discussionmentioning
confidence: 81%
“…Whereas vasovagal syncope is associated with good prognosis,15 increased mortality for cardiac syncope and for syncope in patients with non-cardiac life-threatening illnesses17 has been demonstrated. It appears, however, that it is not the cause of syncope that imparts increased mortality risk, but age and comorbidities, including cardiovascular comorbidity 18 19. This ties in with the fact that a history of myocardial infarction, heart failure and high CCI are all predictors of syncope post pacemaker implant in our population.…”
Section: Discussionmentioning
confidence: 81%
“…11 Rather, underlying heart disease, especially congestive heart failure, was found to be the significant survival predictor. Similarly, a study of hospitalized syncope patients 12 found that the risk of dying was not associated with cardiac cause but correlated with age and comorbid illnesses, which included cardiovascular diseases. In a study of patients with advanced heart failure, poor left ventricular function was associated with high risk of sudden death regardless of the cause of syncope.…”
Section: Prognosis and Risk Stratificationmentioning
confidence: 99%
“…Getchell et al studied elderly hospitalised patients (mean age 73 years) presenting with syncope, and showed that mortality was not associated with a cardiac cause for syncope, but rather with age and comorbid illnesses. 33 Subsequent studies controlling for cardiac mortality have showed that the higher mortality in patients with syncope due to a cardiovascular cause is largely related to underlying cardiovascular disease. 7 21 34 A study comparing patients with and without syncope, who were matched for cardiac disease, showed that syncope itself was not a significant predictor of 1 year survival, 21 however male sex, age .55 years and congestive heart failure were significant predictors.…”
Section: Cardiac Markersmentioning
confidence: 99%